Genetic Correction of Sickle Cell Anemia and β-Thalassemia: Progress and New Perspective - Ajay Perumbeti; Punam Malik (The Scientific World Journal)
Gene therapy for β-globinopathies, particularly β-thalassemia and sickle cell anemia, holds promise for the future as a definitive corrective approach for these common and debilitating disorders. Correction of the β-globinopathies using lentivirus vectors carrying the β- or γ-globin genes and elements of the locus control region has now been well established in murine models, and an understanding of "what is required to cure these diseases" has been developed in the first decade of the 21st century. A clinical trial using one such vector has been initiated in France with intriguing results, while other trials are under development. Vector improvements to enhance the safety and efficiency of lentivirus vectors are being explored, while new strategies, including homologous recombination in induced pluripotent cells, for correction of sickle cell anemia have shown proof-of-concept in vitro. Here, a review is provided of the current substantial progress in genetic correction of β-globin disorders.